Evaluating the Nursing Clinical Decision in Hospitals of Kerman University of Medical Sciences Iran after Evidencebased Nursing Education and Comparison with a Control Group - Esmat Nouhi; Asma Abdollah-Yar; Tayebeh Faseehy Harandi (Kerman University of Medical Sciences, 2014)
Background & Objective: In addition to teaching predesigned courses physicians are usually expected to participate directly in designing curriculum during their professional life Today traditional education systems are not sufficient for developing the expected competencies in physicians One of the applications of new advancements by cognitive science in curriculum design is the development of strategies for improving the quality of the undergraduate medical education curriculum Educational strategies are "fundamental oriented decisions in teaching that are aimed to achieve educational goals"   Methods: This article was a narrative review that introduced and explained the most important educational strategies in undergraduate medical curriculum through surveying valid electronic and library resources   Results: Now the most important educational strategies in undergraduate medical curriculum are a series of studentcentered problembased learning integrated or interprofessional teaching communitybased electivedriven and systematic strategies (SPICES) and also a set of strategies that are productfocused relevant interprofessional short courses multisite locations and symbiotic (PRISMS) and a group of realistic integrated feedback learning and evaluation strategies (RIFLE) as well   Conclusion: Each strategy is represented as a spectrum In each spectrum the educational planner must define the position of every component of the curriculum In order to apply these strategies the curriculum must be intervened according to the selected strategy so that the results of the evaluations and the evidence of interventions ensure the planners that the quality of the curriculum is improved